Talking about torture: how political discourse shapes the debate - Del Rosso, Jared (Columbia Univ. Press, 2015)
Preface -- Introduction -- The torture word -- The heartbreak of acknowledgment : from Metropolitan Detention Center to Abu Ghraib -- Isolating incidents -- Sadism on the night shift : accounting for Abu Ghraib -- "Honor bound" : the political legacy of Guantanamo -- The toxicity of torture : waterboarding and the debate about "enhanced interrogation" -- From "enhanced interrogation" to drones : U.S. counterterrorism and the legacy of torture